Profil internalisasi pendidikan karakter dalam pembelajaran matematika di SD - Dewi Ariyanti; Riyadi Riyadi; Siti Kamsiyati (Universitas Sebelas Maret, 2022)
This study aims to describe the profile of the internalization of character education which is limited to honest and disciplined characters in learning mathematics at SD Negeri 1 Kalinanas Boyolali in the 2020/2021 school year. One way to internalize honest and disciplined character values is through the role of the teacher. Teachers are parents of students in a school environment. So the role of the teacher is so meaningful in shaping the personality of students outside of the influence of their environment. The method used in this research is descriptive qualitative method. The phenomological approach is the research approach used by researchers. Primary data sources are the results of interviews and subject observations. The student character assessment document became a secondary source of research. Data collection techniques using interviews, observation and document study. Technique triangulation is a technique that is done by checking data with the same source but with different techniques. Furthermore, the results of the document analysis were compared with the interviews and observations made to the teacher. The data analysis technique used three stages, namely data reduction, data presentation, and data verification. The results showed that the subjects had met 8 of the 10 indicators of the internalization process of honest and disciplined values in mathematics learning at SD Kalinanas Boyolali in the 2020/2021 academic year. There are two obstacles experienced by research subjects.